Análisis de la demanda eléctrica del sistema de distribución de bajo voltaje para determinar la cargabilidad del sistema eléctrico de la empresa agrinag ubicada en la parroquia Joseguango bajo del cantón Latacunga en el periodo abril – diciembre 2015 - Taday Álvarez, Cesar Augusto (2016)
This project is part of the study of low-voltage electrical system in the company AGRINAG S.A. therefore this study part from the electrical transformers that serve the charge in the enterpraise, to the farthest point that the circuit is derived, so it was necessary as a first step to survey the electrical charge in each transformer, electrical plans, since the company does not have any such information to carry out this project. Once this information is done the placement of a measurement equipment in this case load analyzers in the four electrical transformers to the company, and later dowload the imformation to Excel, the electrical parameters that were evaluated are voltaje level, active power, apparent power, reactive power, current and the results were compared whit the regulation ARCONEL 004/01….